New Efficient Synthesis of 1,4-Benzodiazepin-5-ones by Catalytic Aza-Wittig Reaction - Wang, Long; Qin, Ru-Qing; Yan, Hong-Ye; Ding, Ming-Wu (Synthesis, 2015)
1,4-Benzodiazepin-5-ones were synthesized in 71–89% yields from 2-isocyanato-N-(2-oxoalkyl)benzamides via a new catalytic intramolecular aza-Wittig reaction. Starting from easily accessible phthalic anhydride and α-arylamino ketones, the corresponding 2-{[(2-oxoalkyl)amino]carbonyl}benzoic acids underwent sequential formation of the acid azide and Curtis rearrangement to give 2-isocyanato-N-(2-oxoalkyl)benzamides that were reacted directly to give the final 2,4-diaryl-3,4-dihydro-5H-1,4-benzodiazepin-5-ones and 4-aryl-2-tert-butyl-3,4-dihydro-5H-1,4-benzodiazepin-5-ones.
Keywords: 1,4-benzodiazepin-5-one; catalytic aza-Wittig reaction; Curtius reaction; acyl azide; isocyanate